2012
DOI: 10.1245/s10434-012-2217-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200b Regulates Cell Proliferation, Invasion, and Migration by Directly Targeting ZEB2 in Gastric Carcinoma

Abstract: miR-200b regulates ZEB2 expression and thus controls metastasis in gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 38 publications
9
108
0
Order By: Relevance
“…To determine whether miR-335 directly targets ZEB2, a dual-luciferase reporter assay was performed; it was revealed that miR-335 significantly decreased the luciferase activity ZEB2, a member of the zinc finger family, functions as a transcriptional repressor of E-cadherin (37). ZEB2 has been identified as upregulated in various types of human cancer, including breast, gastric, head and neck, hepatocellular, ovarian and non-small cell lung carcinoma, and glioma (38)(39)(40)(41)(42)(43)(44). ZEB2 was previously identified as upregulated in PTC cell lines compared with normal thyroid cancer cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether miR-335 directly targets ZEB2, a dual-luciferase reporter assay was performed; it was revealed that miR-335 significantly decreased the luciferase activity ZEB2, a member of the zinc finger family, functions as a transcriptional repressor of E-cadherin (37). ZEB2 has been identified as upregulated in various types of human cancer, including breast, gastric, head and neck, hepatocellular, ovarian and non-small cell lung carcinoma, and glioma (38)(39)(40)(41)(42)(43)(44). ZEB2 was previously identified as upregulated in PTC cell lines compared with normal thyroid cancer cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…This gene belongs to the micro RNA family 200 of non-coding RNAs involved in regulation of cancer progression. miR200b is deregulated in different cancers 24 and its aberrant down-expression is also known to enhance tumor invasion [25][26][27] . Furthermore, a prognostic value of miR-200b in different cancers has been shown [28][29][30] .…”
Section: E Study Of Mir-200b Expression For Ht1080 In Droplets Microfmentioning
confidence: 99%
“…Although a particular miRNA that specifically regulates cancer cell intravasation and extravasation has not yet been identified, it is still believed that these steps may also be regulated by miRNAs. miR-200 family is recognized as a master regulator of the epithelial phenotype by post transcriptionally suppression of the expression of the ZEB1 and ZEB2 EMT-inducing transcription factors in breast [28] and gastric cancer [29]. Acting in the opposite direction, ZEB1 and ZEB2, which promote not only tumor cell dissemination, but also the tumorinitiating capacity, has been shown to transcriptionally repress miR-200 family members, thereby establishing a double negative feedback loop that causes the reinforcement of cells in either the mesenchymal or epithelial state [25].…”
Section: Mirnas and Metastasismentioning
confidence: 99%